Slogan Back to the Quran and Sunnah: Studi Pemikiran Jamaluddin al-Afghani - Syahuri Arsyi (Assosiation of Islamic Education Lecturer of Universitas Jenderal Soedirman, 2021)
This study aims to discuss the thoughts of Jamaluddin al-Afghani (1839-1897), one of the reformers of Islamic modernism in the 19th century. This research is a literature study with a factual-historical approach to find out the flow of al-Afghani's thought development, whether related to the environment or the influences experienced in the course of his thought. The results showed that al-Afghani's Islamic political movement is very unique and different from the others. The movement is carried out with the frame of the slogan